Wigner time delay and spin–orbit activated confinement resonances. (14th August 2017) - Keating, D A; Deshmukh, P C; Manson, S T
Abstract: A study of the photoionization of spin–orbit split subshells of high- Z atoms confined in C60 has been performed using the relativistic-random-phase approximation. Specifically, Hg@C60 5p, Rn@C60 6p and Ra@C60 5d were investigated and the near-threshold confinement resonances in the j  =  l  − 1/2 channels were found to engender structures in the j  =  l  + 1/2 cross sections via correlation in the form of interchannel coupling. These structures are termed spin–orbit induced confinement resonances and they are found to profoundly influence the Wigner time delay spectrum resulting in time delays of tens or hundreds of attoseconds along with dramatic swings in time delay over small energy intervals. Pronounced relativistic effects in time delay are also found. These structures, including their manifestation in time delay spectra, are expected to be general phenomena in the photoionization of spin–orbit doublets in confined high- Z atoms.